The Complexity of Learning Chemistry: Methodology for Problem Solving - Novina Mljkovic; Vojer Mljkovic (International Journal of Science and Society, 2019)
In order to study chemistry, it is very important to establish a connection between theory and practice. The ability to solve problems is a well-studied theoretical knowledge and a good methodology for working on theory lessons. Typically, a problem-solving strategy consists of three parts: examining the conditions of the activity and its analysis, forming opinions, completing tasks, and reviewing. To better understand the importance and usefulness of methodological preparation in problem solving, we have assembled two groups of fourteen students from second-grade agricultural engineers. The first group of students has the opportunity to methodically explain the approaches to problems in chemistry. The second group only gets problems that have to be solved without methodical preparation. The purpose of our experimental work is to determine the contribution of methodological preparation during the completion of the activities. The group of students who received the methodically described training achieved significantly better results. This is proof of the assumption in the theoretical part that the methodological preparation of problem solving is unavoidable and necessary, and that its practical significance is multiplied.